2017
DOI: 10.1186/s40645-016-0116-3
|View full text |Cite
|
Sign up to set email alerts
|

Seismic and inter-seismic ground surface deformations of the Murono mud volcano (central Japan): a laser scanning approach

Abstract: A small mud volcano in Murono, Niigata Prefecture, north-central Japan, shows active ground surface displacements, not only when large earthquakes occur in the region but also during quiescent periods between earthquake events. The site recently underwent abrupt deformations due to strong regional earthquakes in 2004, 2007, 2011, and 2014, while gradual surface deformations were reported during quiescent periods between the earthquakes. To detect the spatial distribution of the changes in the mud volcano's gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Recent landscape changes can also be captured via high-definition platforms, such as TLS and UAS to produce new insights into landscape evolution in area experiencing seismic activity. TLS was used to detect subtle ground displacement at a centimeter scale in a mud volcano (Hayakawa et al 2017). An active mud volcano often reacts to a large seismic shake with its surface uplift, but the authors revealed that the mud volcano also actively "breathe" with frequent uplift and subsidence even when no shake is present in the region.…”
Section: Prefacementioning
confidence: 99%
“…Recent landscape changes can also be captured via high-definition platforms, such as TLS and UAS to produce new insights into landscape evolution in area experiencing seismic activity. TLS was used to detect subtle ground displacement at a centimeter scale in a mud volcano (Hayakawa et al 2017). An active mud volcano often reacts to a large seismic shake with its surface uplift, but the authors revealed that the mud volcano also actively "breathe" with frequent uplift and subsidence even when no shake is present in the region.…”
Section: Prefacementioning
confidence: 99%